Automation Tool For Customer Relationship Management Applications - Pokale, Rahul Pandurang; GS, Nagaraja (International Journal of Computer Sciences and Engineering, 2021)
Testing is one of the most important phases in Software Development Life Cycle (SDLC). To test any CRM application such as Salesforce and Siebel, Test engineer pretends as an end user of the system and checks whether the application is working as expected. Test engineer may need to test hundreds of test data combinations to ensure the correctness of the software. The same functionality might be needed to test again with the same test dataset as the changes are made to the software. This paper discusses how we can use Salesforce APIs and Siebel web services to reduce the time required for test data set up and retesting. In this paper firstly the importance of Salesforce and Siebel web services is explained. Then the detailed explanation of the tool is given under the Methodology section and finally experimental results are discussed.